FINANCIAL PROBLEM SOLVING IN A CONSTRUCTION COMPANY USING FUZZY ANALYTIC HIERARCHY PROCESS (FUZZY AHP) - Annisa, Khansa
PT X is a construction company with clients spread among Central Java, West Java, Papua, Kalimantan, and Sulawesi. This company experienced financial problem since Covid-19 until 2023 in the form of an inability to cover expenses. The absence of financial records makes it difficult to determine the cause of financial problems. The owners and managers of PT This research was conducted to find the root cause of the financial problems felt at PT X and to find the best solution to solve them.